Kerohanian Sejagat: Satu Perspektif terhadap Ajaran Universal Sufism - Nozira Salleh; Faudzinaim bin Hj. Badaruddin; Dato' Zakaria Stapa (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Universal spiritual teachings are still neglected by most Islamic scholars due to the thought that the teachings do not have a great influence to Muslims. But in reality, these teachings won the hearts of Muslims in many Islamic countries such as Indonesia, Turkey, Pakistan and others. Therefore, this article attempts to describe this fact by focusing the discussion on the teachings of Universal Sufism, as one of the universal spiritual teachings that are increasingly getting attention of Muslims in particular and mankind in general. The description also involves the assessments based on the Quran as the main guide of Muslims, which is expected to establish a clear understanding of Muslims about the spiritual teachings that are justified and not justified by the Islamic Shari'a.